Effect of eyestalk ablation on moulting and growth in the penaeid shrimp Metapenaeus monoceros (Fabricius, 1798) - Venkitaraman, P R; Jayalakshmy, K V; Balasubramanian, T (Indian Journal of Fisheries, 2016)
Penaeid shrimps (Metapenaeus monoceros) of two different size ranges were subjected to eyestalk ablation both unilaterallyand bilaterally. The unilateral eyestalk ablated (UEA) shrimps consumed 8.9 % (35-40 mm) and 29.9 % (65-70 mm) morefood than control shrimps whereas bilateral eyestalk ablated (BEA) shrimps consumed 18.7% and 31.8% less than thecontrol group in the two size ranges respectively. Growth was estimated as length and weight increments and significantvariation (p